"Leftover Women" and "Kings of the Candy Shop": Gendering Chinese American Ancestral Homeland Migration to China. (September 2017) - Wang, Leslie K.
A growing body of research examines the experiences of highly skilled individuals who "return" to work in their ancestral homeland, but has tended to overlook the gendered dynamics that shape their decisions. This article fills this gap by analyzing how the gendered local context of China affects the experiences of American-Born Chinese (ABC) migrants. Through in-depth qualitative interviews with 52 second-generation ABC professionals in Beijing and Shanghai, I found that both women and men enjoyed comparable career growth and opportunities. Socially, however, men's foreign citizenship, education, and higher wages transformed them into highly eligible dating and marriage partners, while ABC women were stigmatized as "leftover women" (a social category ascribed to urban, educated single women in China). Thus, ABC women must prioritize either their professional or personal lives, while their male counterparts can enjoy both. By highlighting the personal realm, this case reveals how the trajectories of first-world ancestral homeland migrants are uniquely gendered.